2005
DOI: 10.5175/jswe.2005.200303110
|View full text |Cite
|
Sign up to set email alerts
|

Study Abroad and Values Development in Social Work Students

Abstract: Abstract:This article presents results of a qualitative study of values development in U.S. and Scottish social work students who participated in a study-abroad program. Six themes emerged: opening the mind to new ways of thinking; awareness and insight into one's own values and beliefs; social awareness and challenges to societal values and beliefs; appreciation of difference, cultural sensitivity, and anti-discriminatory practice; social justice; and professional identity development. Implications for social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 12 publications
7
87
0
Order By: Relevance
“…Studies have shown that students who study abroad develop a deeper understanding and respect for global issues (Carsello and Creaser 1976;Carlson et al 1990;Douglas and Jones-Rikkers 2001), more favorable attitudes toward other cultures (Carlson and Widaman 1988;Kitsantas 2004), stronger intercultural communication skills (Anderson et al 2006;Williams 2005), improved personal and professional self image (Cushner and Mahon 2002), and better foreign language skills (Brecht et al 1993;Freed 1995). In addition, surveys of former study abroad participants consistently indicate that they believe the experience improved their self-confidence, ability to handle ambiguity, insight into their own value systems, and overall maturity (Carlson et al 1990; Institute for the International Education of Students 2004; Lindsey 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that students who study abroad develop a deeper understanding and respect for global issues (Carsello and Creaser 1976;Carlson et al 1990;Douglas and Jones-Rikkers 2001), more favorable attitudes toward other cultures (Carlson and Widaman 1988;Kitsantas 2004), stronger intercultural communication skills (Anderson et al 2006;Williams 2005), improved personal and professional self image (Cushner and Mahon 2002), and better foreign language skills (Brecht et al 1993;Freed 1995). In addition, surveys of former study abroad participants consistently indicate that they believe the experience improved their self-confidence, ability to handle ambiguity, insight into their own value systems, and overall maturity (Carlson et al 1990; Institute for the International Education of Students 2004; Lindsey 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Interrogating one's own personal values, and understanding how they interact with professional ones, is considered imperative for professional identity (Lindsey, 2005;Wong and Pearson, 2007). This requires challenging identity work: Wiles found that students talked about their developing professional identities as a source of tension in their changing relationships with family and friends.…”
Section: Meanings Of Professional Identity: a Resource For Students' mentioning
confidence: 99%
“…Study abroad participation has been linked with aspects of psychosocial -often called personal -development (Gmelch, 1997;Gullahorn & Gullahorn, 1966;Kauffmann, 1983;Milstein, 2005), identity development (Dolby, 2004;Talburt & Stewart, 1999), moral or values development (Jurgens & McAuliffe, 2004;Lindsey, 2005;Ryan & Twibell, 2000), intellectual development (Barrutia, 1971;McKeown, 2009;Zhai & Scheer, 2002), and holistic development conceptualized as self-authorship (Braskamp, Braskamp, & Merrill, 2009;Du, 2007). Most prominent among the educational benefits claimed of an international educational experience, study abroad has long been considered a powerful mechanism for developing intercultural competence (Fulbright, 1989;Hoffa, 2007;Hoffa & DePaul, 2010;Lincoln Commission, 2005;NAFSA, 2003; National Task Force on Undergraduate Education Abroad, 1990).…”
Section: Study Abroad and Intercultural Competencementioning
confidence: 99%